2017
DOI: 10.3920/wmj2016.2107
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds inDiospyros mafiensis roots inhibit growth, sporulation and aflatoxin production byAspergillus flavus andAspergillus parasiticus

Abstract: Diospyros mafiensis F. White is a medicinal shrub or small tree (6 m tall) widely distributed in the Zanzibar-Inhambane regional mosaic and traditionally used to treat leprosy, diarrhoea, and skin fungal infections in Tanzania and Mozambique. Our objective was to determine the anti-aflatoxigenic properties of compounds from D. mafiensis root bark against vegetative growth, sporulation and aflatoxin production by Aspergillus flavus and Aspergillus parasiticus. Bioassay-guided extraction, fractionation, and isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Arguably, this sends the message that weak inhibition of vegetative growth of a certain fungal strain does not necessarily mean weak inhibition of aflatoxin formation. This is consistent with Mmongoyo et al (2017) who found out that although extracts and diosquinone from D. mafiensis weakly suppressed fungal growth, they inhibited aflatoxin production strongly even at lower doses. Similarly, the D. capricornuta stem-bark methanolic extracts strongly inhibit toxin production in A. flavus, particularly at the dose of 250 µg/mL by over 99% and A. parasiticus by 94%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Arguably, this sends the message that weak inhibition of vegetative growth of a certain fungal strain does not necessarily mean weak inhibition of aflatoxin formation. This is consistent with Mmongoyo et al (2017) who found out that although extracts and diosquinone from D. mafiensis weakly suppressed fungal growth, they inhibited aflatoxin production strongly even at lower doses. Similarly, the D. capricornuta stem-bark methanolic extracts strongly inhibit toxin production in A. flavus, particularly at the dose of 250 µg/mL by over 99% and A. parasiticus by 94%.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the D. capricornuta stem-bark methanolic extracts strongly inhibit toxin production in A. flavus, particularly at the dose of 250 µg/mL by over 99% and A. parasiticus by 94%. This phenomenon of inhibitors from the herbal extracts strongly inhibiting fungal toxin production without severely inhibiting their mycelial growth has been reported (Bhatnagar and McCormick 1988, Jayashree and Subramanyam 1999, Mmongoyo et al 2017. Since the aflatoxigenic fungi produce aflatoxins via a complex biochemical system called aflatoxin biosynthesis (Yu et al 2004), the mode of action of the extracts to inhibit the fungi to produce aflatoxins is associated with their inherent abilities to block aflatoxin biosynthesis and stop aflatoxin production completely (Holmes et al 2008).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have reported the potential antifungal activity of the root and root bark of most Diospyros species [42,54,92]. However, the antifungal activity of a leaf extract of D. mespiliformis has also been confirmed [47,93].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The antiaflatoxigenic activity of D. mafiensis root, another Mozambican medicinal plant, has been linked to the presence of diosquione and 3-hydroxydioquinone, making this herbal drug also an important natural antifungal for preventing fungal growth and aflatoxin accumulation in food [42]. In addition, this species has also been found to have analgesic, antidiabetic, anti-inflammatory, and antioxidant effects, likely correlated with the presence of these kind of constituents.…”
Section: Antifungal and Antiviral Activitiesmentioning
confidence: 99%